Analysis of Back-End Requirements of a Web-Based Application to Identify Damage for Building Structures - A Anisya; Fajar Nugroho (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The need for well-maintained facilities can certainly affect activities in the building. To meet these needs, a building maintenance work program is needed to achieve the planned life of the building. The problem with contractors is that they still use telephone communication to receive reports of any damage to the building. This paper discusses the needs analysis in the construction of a building damage reporting system from the back-end side. The application is built on a web-based basis and provides information about the building in terms of the structural aspect as well as grouping the damage based on the damage criteria. The results of this study are obtained in the form of 10 tables that will compile a system database and transaction analysis that can be done in the system, namely generating building damage data reports where there are four categories of damage, namely light damage, moderate damage , severe damage, total damage and this application can later be used by building managers in reporting building damage through applications and contractors can monitor through applications